COMPARATIVE LAW OF ISLAMIC INHERITANCE AND CIVIL LAW INHERITANCE (WEST) - Amine El Khalfi; Ong Argo Victoria; Fareha Binti Moh. Zukri (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
Talking inheritance law can not be separated from some of the elements that are bound. The elements are as follows: 1) The Heir, heir is the person who died or people who give so-called legacy heir. Usually heir bestows both wealth and debt obligations or to other persons or heirs. 2) The heirs, heirs are those who inherit referred to as heir was given the legal right to receive the assets and liabilities or debts left by the testator. 3) Treasure heritage, heritage is everything that is given to the heir to the testator possessed, whether it be right or property such as houses, cars, and gold as well as liability for the debt. But, despite its importance, is often the subject of this heritage be problematic. Not surprisingly, many people who dropped the ropes brotherhood because of inheritance. The main problems are usually due to disagreements about equality and fairness. Indonesia has two Inheritance law, they are based on Islamic law (Faraidh) and Civil Law (Penal Code).